2021
DOI: 10.1038/s41378-020-00228-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanodroplet-mediated catheter-directed sonothrombolysis of retracted blood clots

Abstract: One major challenge in current microbubble (MB) and tissue plasminogen activator (tPA)-mediated sonothrombolysis techniques is effectively treating retracted blood clots, owing to the high density and low porosity of retracted clots. Nanodroplets (NDs) have the potential to enhance retracted clot lysis owing to their small size and ability to penetrate into retracted clots to enhance drug delivery. For the first time, we demonstrate that a sub-megahertz, forward-viewing intravascular (FVI) transducer can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Bubble activity is the primary catalyst to promote clot degradation [ 12 ]. Most sonothrombolysis schemes employ exogenous agents such as microbubbles, nanobubbles, or droplets to nucleate bubble activity [ 17 , 18 ]. These methods have a limited thrombus penetration profile [ 19 ] and do not sustain bubble activity for extended periods (< 30 s) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bubble activity is the primary catalyst to promote clot degradation [ 12 ]. Most sonothrombolysis schemes employ exogenous agents such as microbubbles, nanobubbles, or droplets to nucleate bubble activity [ 17 , 18 ]. These methods have a limited thrombus penetration profile [ 19 ] and do not sustain bubble activity for extended periods (< 30 s) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 ). Fresh microbubbles can enter the ultrasonic field during the durations when there is no high-energy pulsing [ 157 ].…”
Section: Novel Microbubble-based Treatment In Biomedicinementioning
confidence: 99%
“…Clinically, it has been reported that low recanalization rates and higher number of retrieval attempts are associated with brin-rich clots [4]- [8]. It is hypothesized that the mechanical properties of the clots result in different resistance of clots to the thrombolytic treatment: the retracted or brin-rich clots are stiffer and denser than the unretracted or erythrocytes-rich clots, and therefore has lower thrombolysis e ciency [6], [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no clot characterization using PA imaging in deep tissue, limited by the external light illumination in conventional PACT. There is only a few reported works on USguided intravenous sonothrombolysis [8], [9], [37]. As deep veins are typically several centimeters away from the skin surface, external light illumination provides limited imaging depth due to strong optical scattering of tissue.…”
Section: Introductionmentioning
confidence: 99%